2008
DOI: 10.1158/0008-5472.can-07-5558
|View full text |Cite
|
Sign up to set email alerts
|

C-Myc Is a Critical Mediator of the Phenotypes of Apc Loss in the Intestine

Abstract: The Adenomatous polyposis coli (Apc) gene is mutated in up to 80% of sporadic colorectal cancers. After Apc loss, there is deregulation of the Wnt signaling pathway and transactivation of T-cell factor/leukemia enhancing factor target genes such as C-Myc. This review focuses on recent data highlighting the importance of the C-Myc oncogene and its transcriptional targets in establishing all of the phenotypes caused by the deletion of the Apc tumor suppressor gene within the intestinal epithelium. The importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 31 publications
2
53
0
Order By: Relevance
“…There has been much debate over whether c-Myc is a therapeutic target for colorectal cancer and the difficulties regarding targeting c-Myc using small molecules (Soucek et al, 2008;Wilkins and Sansom, 2008). Our study here suggests that reduction of c-Myc (as well as complete ablation) may be a rationale for chemoprevention of colorectal cancer.…”
mentioning
confidence: 71%
“…There has been much debate over whether c-Myc is a therapeutic target for colorectal cancer and the difficulties regarding targeting c-Myc using small molecules (Soucek et al, 2008;Wilkins and Sansom, 2008). Our study here suggests that reduction of c-Myc (as well as complete ablation) may be a rationale for chemoprevention of colorectal cancer.…”
mentioning
confidence: 71%
“…Moreover, we also found that RNAi-mediated downregulation of RCK/p54 expression could significantly reduce the Tcf transcriptional activity and the expression levels of the known Wnt target gene such as β-catenin, c-Myc, cyclinD1, cox-2, Livin, survivin and VEGF. [26][27][28][29][30][31][32] Thus, we conclude that the overexpression of RCK/p54 takes part in the activation of Wnt signaling pathway and transmits the canonical Wnt signals to downstream molecules despite the presence of APC mutation, which seem to be compatible with the "just right" chemically synthesized (BioAsia bioengineering Inc., Shanghai, China) and then annealed to form double-stranded cDNA fragments that were inserted between the BamHI and HindIII sites of linearized pSilencer4.1-CMVneo vector (Ambion, USA) downstream of CMV promoter according to the manufacturer's instructions ( Fig. 2A).…”
Section: Methodsmentioning
confidence: 99%
“…c-myc is believed to participate in most aspects of cellular function, including replication, growth, metabolism, differentiation, and apoptosis [6][7][8]. A frequent genetic abnormality seen in colon cancer is the elevated expression of c-myc [4,9]. The importance of c-myc expression in colon cancer has been demonstrated in both studies of transgenic mice and clinical research [10,11].…”
Section: Introductionmentioning
confidence: 99%